2001
DOI: 10.1038/sj.jp.7210634
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Brain Toxicity

Abstract: Bilirubin is toxic in most biological systems tested. Several mechanisms have been suggested for this toxic effect, including inhibition of enzyme systems and inhibition of cell regulatory reactions (protein/peptide phosphorylation). The identity of the basic mechanism(s) has not been conclusively proven, but inhibition of peptide phosphorylation, perhaps mediated or modulated by lysine at the active site(s), appears to be compatible with many of the observations currently found in the literature. Bilirubin en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 24 publications
0
27
0
4
Order By: Relevance
“…The best-fitting models and the estimated relative risks of RHD MFG incompatibility are consistent with the hypothesized effect of previous incompatible pregnancies on the risk of schizophrenia due to RHD MFG incompatibility, namely that previous incompatible pregnancies increase the risk of Rh incompatibility disease. The hypothesized role of Rh incompatibility disease in schizophrenia risk is consistent with the neurodevelopmental 24 and glial asthenia 13 hypotheses of schizophrenia, as Rh incompatibility disease can lead to fetal hypoxia and an increase in unconjugated bilirubin, 8,9 a neurotoxin than can damage undifferentiated glial cells. 10,11 A previously published analysis of the same set of nuclear families that used only the youngest affected child in each nuclear family reported a one-sided P-value of 0.027.…”
Section: Discussionmentioning
confidence: 59%
“…The best-fitting models and the estimated relative risks of RHD MFG incompatibility are consistent with the hypothesized effect of previous incompatible pregnancies on the risk of schizophrenia due to RHD MFG incompatibility, namely that previous incompatible pregnancies increase the risk of Rh incompatibility disease. The hypothesized role of Rh incompatibility disease in schizophrenia risk is consistent with the neurodevelopmental 24 and glial asthenia 13 hypotheses of schizophrenia, as Rh incompatibility disease can lead to fetal hypoxia and an increase in unconjugated bilirubin, 8,9 a neurotoxin than can damage undifferentiated glial cells. 10,11 A previously published analysis of the same set of nuclear families that used only the youngest affected child in each nuclear family reported a one-sided P-value of 0.027.…”
Section: Discussionmentioning
confidence: 59%
“…It was reported that biliary excretion is the rate-limiting step of bilirubin elimination. At high intracellular concentrations, bilirubin can uncouple oxidative phosphorylation, reduce DNA stability, interrupt protein synthesis, and block ATPase activity in brain mitochondria (Hansen, 2001). Therefore, hyperbilirubinemia may provide an early warning of possible adverse effects, such as neurotoxicity and hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…When accumulated at abnormally high concentrations in early life, bilirubin is toxic and is responsible for the clinical symptoms of kernicterus. 12 However, the antioxidant nature of the bile pigments suggests potential beneficial effects as well. 13 Furthermore, there is accumulating evidence from epidemiological studies that individuals with highnormal or just above normal plasma bilirubin levels, including individuals with Gilbert syndrome, have a lesser incidence of coronary heart disease and carotid plaque formation.…”
mentioning
confidence: 99%